Evaluation of occupational and patient dose in cerebral angiography procedures - Lunelli,Neuri Antonio (2013)
Objective The present study was aimed at estimating the doses received by physicians and patients during cerebral angiography procedures in a public hospital of Recife, PE, Brazil. Materials and Methods The study sample included 158 adult patients, and during the procedures the following parameters were evaluated: exposure parameters (kV, mAs), number of acquired images, reference air kerma value (Ka,r) and air kerma-area product (PKA). Additionally, the physicians involved in the procedures were evaluated as for absorbed dose in the eyes, thyroid, chest, hands and feet. Results The results demonstrated that the doses to the patients' eyes region were relatively close to the threshold for cataract occurrence. As regards the physicians, the average effective dose was 2.6 µSv, and the highest effective dose recorded was 16 µSv. Conclusion Depending on the number of procedures, the doses received by the physicians may exceed the annual dose limit for the crystalline lenses (20 mSv) established by national and international standards. It is important to note that the high doses received by the physicians are due to the lack of radiation protection equipment and accessories, such as leaded curtains, screens and protective goggles.